Occupational Purposes model designed for workplace language training in Costa Rica - Rodríguez, Xinia (2013)
This article reports on a pioneering language training program in English for Occupational Purposes, piloted in seven multinationals in Costa Rica. The researcher, one of the core trainers, analyzes a job performance task, crucial for the training participants, and explains the use of authentic tasks and framework materials.